Physical Factors Optimization of Saccharomyces cerevisiae Fermentation to Enhance Production of Bioethanol: A Review - Muhamad, Aida; Mohd Noor, Siti Fatimah; Nurul Syahirah; Hamid, Aliff Imran; Mohd Zaidi, Muhammad Aiman Harris (Multidisciplinary Applied Research and Innovation, 2021)
The high demand for fossil fuels will reduce the world fuel reserve and may lead to the shortage and price increase of the fuel. To overcome this scenario, alternative energy such as renewable energy can reduce the reliance on limited fossil fuels. This review paper attempts to gather the research findings for biofuel production using biomass through fermentation process that dependant on various physical factors. The Saccharomyces cerevisiae (S. cerevisiae) is the favored choice for ethanol fermentation due to its ability to ferment a wide range of sugars. It is also discovered that great sources of sugar can be acquired from the waste of oil palm. Oil palm trunk (OPT) is rich in moisture content and sugar component. Therefore, this review focused on optimizing the fermentation physical factors such as pH, temperature, incubation period, concentration of inoculum and agigation speed to produce high yield of bioethanol from OPT through fermentation process.